2019
DOI: 10.3390/cells8101243
|View full text |Cite
|
Sign up to set email alerts
|

The Bright and Dark Side of DNA Methylation: A Matter of Balance

Abstract: DNA methylation controls several cellular processes, from early development to old age, including biological responses to endogenous or exogenous stimuli contributing to disease transition. As a result, minimal DNA methylation changes during developmental stages drive severe phenotypes, as observed in germ-line imprinting disorders, while genome-wide alterations occurring in somatic cells are linked to cancer onset and progression. By summarizing the molecular events governing DNA methylation, we focus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 136 publications
0
14
0
Order By: Relevance
“…DNA methylation results from the covalent transfer of a methyl group from S-adenosyl-L-methionine to cytosine in CpG dinucleotides [29]. Promoter regions of genes have high GC contents, which are called CpG islands, and these may be methylated [30].…”
Section: Htlv-1 Dna Methylationmentioning
confidence: 99%
“…DNA methylation results from the covalent transfer of a methyl group from S-adenosyl-L-methionine to cytosine in CpG dinucleotides [29]. Promoter regions of genes have high GC contents, which are called CpG islands, and these may be methylated [30].…”
Section: Htlv-1 Dna Methylationmentioning
confidence: 99%
“…The role of DNA methylation in cancer has been the topic of intensive study during the recent years. Since the discovery of DNA methylation mechanisms, a large part of the literature has reported that DNA methyltransferase aberrant activity is present in tumors [10][11][12][13][14][15]. It has been found that malignant cells often manifest increased total DNA methyltrasferase activity, significantly extensive loss of methylation, from otherwise physiologically methylated promoters, but also hypermethylation of normally unmethlylated DNA sites [16][17][18][19][20].…”
Section: Dna Methylation and Cancermentioning
confidence: 99%
“…DNA methylation is characterized by the covalent addition of a methyl group to the 5’-position of the pyrimidine ring of cytosines by DNA methyltransferases, giving rise to 5-methylcytosine. This enzymatic process occurs predominantly within CpG dinucleotides which are concentrated at CpG-rich DNA stretches named CpG islands (CGIs), which overlap the promoter region of 60–70% of protein-coding genes [ 14 ]. In the human genome, approximately 80% of CpG dinucleotides are heavily methylated whereas CGIs in gene promoters are mostly unmethylated, allowing active gene transcription [ 13 ].…”
Section: Introductionmentioning
confidence: 99%